Kesadaran Mahasiswa Pendidikan Ekonomi terhadap Pentingnya Mengonsumsi Air Mineral bagi Kesehatan Tubuh di Era Inovasi Minuman Instan - Meisya Putri Izati; Salmadila Ramadhanty; Supriyono Supriyono (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research is based on the number of Economics Education students who when they finish doing activities or learning, where in that condition they will feel thirsty and need a drink, but they prefer to consume instant drinks rather than mineral water. Thus, the purpose of this study is to analyze the awareness of Economic Education students of the importance of consuming mineral water compared to instant drinks. Basically, humans as living things really need calcium, sodium, selenium, potassium, silica, and zinc which are very beneficial for the health of the body, these contents are found in mineral water. This research is a quantitative study with a questionnaire method that focuses on Economics Education students.